The Influence of Excitement and Sophistication on Brand Trust Through Brand Image as an Intervening Variable (Study on Shopee Users in Surabaya) - Ananda Leony; Rusdi Hidayat Nugroho (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Abstract